(untitled) (IPS Journal of Toxicology, 2025)
Persistent Organic Pollutants (POPs), particularly polycyclic aromatic hydrocarbons (PAHs) such as benzo(a)pyrene and naphthalene, disrupt inflammatory homeostasis and exacerbate oxidative stress. This study evaluated the synergistic effects of PAHs and hydrogen peroxide (H₂O₂)-induced oxidative stress on inflammatory markers in Wistar rats for four weeks (Batch one) and eight weeks (Batch two) exposure durations, alongside the ameliorative potential of vitamin C. Key markers analyzed included tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1 beta (IL-1β), and interleukin-10 (IL-10). In Batch one, H₂O₂-only exposure significantly elevated TNF-α (6690.62 ± 0.01 pg/mL), IL-6 (701.94 ± 0.01 pg/mL), and IL-1β (2679.39 ± 0.01 pg/mL) compared to the control group (3999.89 ± 0.01, 490.55 ± 0.01, and 1705.44 ± 0.01 pg/mL, respectively). Batch two results showed further increases, with TNF-α reaching 6900.83 ± 0.01 pg/mL and IL-6 rising to 725.21 ± 0.01 pg/mL, indicating cumulative inflammatory effects over time. High-dose H₂O₂ combined with PAHs elevated TNF-α from 3980.79 ± 0.01 pg/mL in Batch one to 4100.25 ± 0.01 pg/mL in Batch two. Vitamin C treatment further amplified TNF-α levels in both batches, peaking at 18340.93 ± 0.02 pg/mL in Batch one and 18750.23 ± 0.02 pg/mL in Batch two, while partially mitigating IL-6 and IL-10 levels. These findings underscore the complex interplay between oxidative stress, inflammation, and antioxidant dynamics under POP exposure. The progressive nature of inflammatory responses highlights the need for early intervention and the potential of combination therapies to mitigate environmental pollutant-induced inflammation.